2017
DOI: 10.1111/jpn.12644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porcine glucagon‐like peptides‐2 on tight junction in GLP‐2R + IPEC‐J2 cell through the PI3k/Akt/mTOR/p70S6K signalling pathway

Abstract: Because of rare glucagon-like peptide-2 (GLP-2) receptor (+) cells within the gut mucosa, the molecular mechanisms transducing the diverse actions of GLP-2 remain largely obscure. This research identified the naturally occurring intestinal cell lines that endogenously express GLP-2R and determined the molecular mechanisms of the protective effects of GLP-2-mediated tight junctions (TJ) in GLP-2R (+) cell line. (i) Immunohistochemistry results showed that GLP-2R is localised to the epithelia, laminae propriae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…p70S6K is a downstream target of mTOR kinase (32), and studies have demonstrated that p-mTOR activates p-p706S kinase, leading to p-S6 activation (33,34). Our results showed that flaccidoxide-treated cells had lower expression levels of p-mTOR, as well as reduced expression of its downstream targets, p-p706SK, p-S6 and p-eIF4B.…”
Section: Resultssupporting
confidence: 51%
“…p70S6K is a downstream target of mTOR kinase (32), and studies have demonstrated that p-mTOR activates p-p706S kinase, leading to p-S6 activation (33,34). Our results showed that flaccidoxide-treated cells had lower expression levels of p-mTOR, as well as reduced expression of its downstream targets, p-p706SK, p-S6 and p-eIF4B.…”
Section: Resultssupporting
confidence: 51%
“…GLP-2 supplementation has not yet been employed to modify intestinal microbiotas, but most studies have primarily focused on investigating the effects of GLP-2 on the regulation of intestinal growth and functions [5,17,18]. Fig.…”
Section: Glp-2 Supplementation Had Better Growth Of Weaned Piglets Bumentioning
confidence: 99%
“…25,26 Moreover, several animal studies have demonstrated that treatment with GLP-2 can improve intestinal barrier function by reducing the gastrointestinal permeability and increasing key markers of tight-junction integrity. 21,27,28 Exogenous GLP-2 has also been shown to stimulate proximal intestinal blood flow, 20 increase the overall splanchnic oxygenation 29 and angiogenesis, 30,31 as well as promote intestinal mucosal growth, 22 thereby enhancing postresectional adaptation. This has been demonstrated to enhance fluid and nutrient absorption as well as reduce malabsorption and diarrhea in both preclinical and clinical SBS settings.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, plasma citrulline, a proposed marker of enterocyte mass, has also been shown to increase in humans following treatment with GLP‐2 25,26 . Moreover, several animal studies have demonstrated that treatment with GLP‐2 can improve intestinal barrier function by reducing the gastrointestinal permeability and increasing key markers of tight‐junction integrity 21,27,28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation